Phytochemical and in vitro and in vivo biological investigation on the antihypertensive activity of mango leaves (Mangifera indica L.). (October 2015) - Ronchi, Silas Nascimento; Brasil, Girlandia Alexandre; do Nascimento, Andrews Marques; de Lima, Ewelyne Miranda; Scherer, Rodrigo; Costa, Helber B.; Romão, Wanderson; Boëchat, Giovanna Assis Pereira; Lenz, Dominik; Fronza, Marcio; Bissoli, Nazaré Souza; Endringer, Denise Coutinho; et al.
Aims: The aim of this study was to investigate the antihypertensive effect of leaves Mangifera indica L. using in vitro and in vivo assays. Methodology: The ethanol extract of leaves of M. indica was fractionated to dichloromethanic, n-butyl alcohol and aqueous fractions. The chemical composition of ethanolic extract and dichloromethanic fraction were evaluated by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Antioxidant activity was evaluated in the DPPH scavenging activity assay. Angiotensin-converting enzyme (ACE) inhibitory activity was investigated using in vitro and in vivo assays. The chronic antihypertensive assay was performed in spontaneously hypertensive rats (SHRs) and Wistar rats treated with enalapril (10 mg/kg), dichloromethanic fraction (100 mg/kg; twice a day) or vehicle control for 30 days. The baroreflex sensitivity was evaluated through the use of sodium nitroprusside and phenylephrine. Cardiac hypertrophy was evaluated by morphometric analysis. Results: The dichloromethanic fraction exhibited the highest flavonoid, total phenolic content and high antioxidant activity. Dichloromethanic fraction elicited ACE inhibitory activity in vitro (99 ± 8%) similar to captopril. LC-MS/MS analysis revealed the presence of ferulic acid (48.3 ± 0.04 µg/g) caffeic acid (159.8 ± 0.02 µg/g), gallic acid (142.5 ± 0.03 µg/g), apigenin (11.0 ± 0.01 µg/g) and quercetin (203.3 ± 0.05 µg/g). The chronic antihypertensive effects elicited by dichloromethanic fraction were similar to those of enalapril, and the baroreflex sensitivity was normalized in SHR. Plasma ACE activity and cardiac hypertrophy were comparable with animals treated with enalapril. Conclusions: Dichloromethanic fraction of M. indica presented an antihypertensive effect, most likely by ACE inhibition, with benefits in baroreflex sensitivity and cardiac hypertrophy. Altogether, the results of the present study suggest that the dichloromethanic fraction of M. indica leaves may have potential as a promoting antihypertensive agent.